2017
DOI: 10.1016/j.clindermatol.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Acral manifestations of soft tissue tumors

Abstract: This group of biologically diverse entities is united by topographic localization to the hands and feet. Categorizing tumors by body site narrows the differential into a short list of possibilities that can facilitate accurate and rapid diagnosis. The goal of this review is to provide a practical approach to soft tissue tumors of acral locations for clinicians, pathologists, and researchers alike. What ensues in the following text is that tight coupling of the clinical picture and histopathologic findings shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
3
0
2
Order By: Relevance
“…A potential explanation should be a statistical histological subtype preponderance of clear cell, epithelioid, and synovial sarcomas, which may affect younger patients with a lower incidence in DESTS sarcomas of myxoid liposarcomas and liposarcomas, usually developing in older patients . Histological preponderance might also explain DESTS male patient preponderance and impact on prognosis compared to women . Distal extremity sarcomas studies also concluded to having worse outcomes in older and male patients .…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation should be a statistical histological subtype preponderance of clear cell, epithelioid, and synovial sarcomas, which may affect younger patients with a lower incidence in DESTS sarcomas of myxoid liposarcomas and liposarcomas, usually developing in older patients . Histological preponderance might also explain DESTS male patient preponderance and impact on prognosis compared to women . Distal extremity sarcomas studies also concluded to having worse outcomes in older and male patients .…”
Section: Discussionmentioning
confidence: 99%
“…A few cases have been described in adults. There is no sex predilection 11 and no suggestion that antecedent trauma may influence its development. It accounts for about 0.1% of fibrous tumours in children.…”
Section: Discussionmentioning
confidence: 99%
“…In a paper presenting ultrasonography findings for soft tissue lesions of the limbs, a proper presumed diagnosis for angiolipomas was reported in 8.3% of 36 angiolipoma cases [4]. Awareness of this tumor is important because of the large numbers of other growths in the differential diagnosis for acral soft tissue tumors, as listed in Table 2 [4,10].…”
Section: Case Discussionmentioning
confidence: 99%